A imago urbis e a aparente lógica da ordem: um estudo de caso na tríplice fronteira - Cabanha, Samuel (2024)
The idea of this thesis is to produce a counter-narrative about what is conceived in/for the city of Foz do Iguaçu - Paraná, specifically, regarding the (re)production of a memory considered univocal and an imago urbis. To do this, I examine the sources, seeking to highlight these discourses, which, for a long time, orbit around a project of memory and identity for the city. As a method, the choice was made by the evidential paradigm, or rather, by ―indicative elements, clues and traces‖ that strengthen the central idea of the thesis and, for this, different sources were selected, such as the judicial process that deals with the occupation Bubas as well as the discourse of the media(s), excerpts from texts published in magazines, newspaper articles, documents, photographs and images. To analyze the sources, I relied on bibliography that is close to discourse analysis, memory and urban critical theory. The fundamental thesis is that the idea of an ―eminently touristic feature‖ intertwines the concepts of vocation-city and company-city, which culminate in the commodity city. The concepts of city-vocation and city-company work interdependently, with an intertwining, uniting them in such a way that one is confused with the other, in whose intertwining, none of these processes is truly isolatable. These concepts are understood as a tool-ideology whose essence is to (re)produce a kind of spectacle city, having as its main basis of action the combination of efforts from different sectors (media(s), tourism, hotel sector, real estate and cultural) who seek to shape the city based on the interests of capital based on a business management model. This action is anchored in a consistent discursive apparatus that impacts the (re)production of memory(s) and the (re)production of management policies for the city that aim to transform urban space as a function of tourism. Locating these discourses is, therefore, a way of denouncing this aspect of the dominant ideology that functions as a political apparatus for (re)producing peripheralization, segregation and, consequently, disqualification and social isolation.